Evaluation of the antibiotics effects on the physical and chemical parameters during the co-composting of sewage sludge with palm wastes in a bioreactor. (October 2017) - Ezzariai, Amine; Barret, Maialen; Merlina, Georges; Pinelli, Eric; Hafidi, Mohamed
Highlights: We assessed antibiotics effects on the thermal, physical and chemical parameters. The highest antibiotics concentrations affected the thermophilic stage. The compost quality is influenced by the highest antibiotics concentrations. Both the mechanical and the biological erosion controlled the composting process. Abstract: The objective of this study was to investigate thermal and physicochemical parameters of sewage sludge-palm waste mixtures contaminated by different families of antibiotics (tetracyclines, macrolides and fluoroquinolones) during co-composting. Sludge was spiked with chlortetracycline (CTC), oxytetracycline (OTC), roxithromycin (RXY), enrofloxacin (ENR) and ciprofloxacin (CIP). Antibiotics were spiked at a low level, medium level, high level and a control without antibiotics was conducted. The results showed that the organic matter degradation was delayed and the carbon/nitrogen (C/N) ratio was affected by an increase of the antibiotics concentration. The presence of antibiotics, especially at high level, delayed the coming of the temperature maxima, and disturbed the thermophilic phase. The calorific model showed that the heat release is affected during the thermophilic phase when high antibiotics concentrations were used. In addition, the microbiological approach showed that the adsorption of antibiotics on the rachis could be probably responsible of the fungi inhibition especially during the maturation phase. Therefore, the medium and high levels of antibiotics affected the thermal, physical and chemical parameters as well as the compost quality.